O19 Are Asian children more likely to develop paediatric inflammatory bowel disease? A study of incidence rates in west Yorkshire. (12th September 2022) - Malik, Anam; Rabone, Rosalind; Zamvar, Veena
Abstract : Introduction and Aims: The incidence of Paediatric Inflammatory Bowel Disease (PIBD) including Ulcerative Colitis, Crohn's and Inflammatory Bowel Disease – Unclassified has been increasing globally and in the United Kingdom. A group of diseases with multifactorial etiology, diet, genetics and environmental factors have all been implicated in the development of PIBD. Traditionally thought of as a Caucasian illness, rates of incidence are stable in North America and Europe, however have been increasing in South East Asia and Africa. Few ethnicity studies have previously investigated the paediatric IBD population. This project aimed to analyse ethnic variations in the incidence of PIBD in West Yorkshire. Methods: This is a retrospective study where data from all new colonoscopies between December 2017 and December 2019 at Leeds Children's Hospital (tertiary centre for Paediatric Gastroenterology in West Yorkshire) were analysed for patients with new diagnosis of PIBD (single user only). Ethnicities were divided into three categories: White British, Asian (including Indian, Pakistani, Bangladeshi and Middle Eastern) and Other (Black Caribbean and Mixed). ONS school pupils' data and ONS West Yorkshire ethnicity population estimates from January 2020 were utilised to calculate incidence rate per ethnic category. Statistical significance was calculated through the Pearson chi-squared test. Results: Out of 157 patients, 75 had newly diagnosed PIBD, 39 patients with Crohn's, 23 with IBD-U and 13 with UC. 21 patients were Asian, 34 were White British and 3 were of Other ethnicities (17 patients did not have their ethnicity documented). Incidence of PIBD in Asian children was 10/100, 000 children per year, White British 7/100, 000 per year and Other 4/100, 000 per year. Asian children have a significantly higher incidence rate of PIBD, taking into account their populations in the West Yorkshire as compared to White British and children from Other ethnicities (p<0.001). Summary: While this a small study group, statistically significant results were found showing ethnic variation in the incidence of PIBD, with Asians having higher incidence rates. This has implications for services; additional investment into community support is required for these patients and their families as these groups are associated with lower socioeconomic backgrounds and possible language barriers. This is consistent with adult studies which have found higher incidences in Indian populations however admittedly, some UK based studies show lower rates of incidence in the Asian population. Conclusion: Our study shows Asians to have a significantly higher incidence of PIBD, however further multi-centre studies are required to explore this and to identity factors that are responsible for the rising incidence of disease.